THE POWER OF SELF-DECEPTION: PSYCHOLOGICAL REACTION TO THE COVID-19 THREAT - Kaczmarek, Bożydar L. J.; Gaś, Zbigniew B. (Acta neuropsychologica (Warszawa), 2021)
Poland’s inhabitants have often expressed disbelief and negative attitudes toward social isolation, combined with restlessness. This is due to a tendency to discount troubling informa tion while facing the unknown and counter-argue against information that causes discomfort and fear. This tendency helps humans to maintain hope and well-being. The study aimed to determine if Polish citizens tend to downplay or even deny danger when faced with a death threat. The study comprised 58 adults – 46 females 12 males, aged 21 to 49. The participants were asked to answer 12 questions defining their beliefs and attitudes towards the COVID-19 pandemic threat and its consequences. The subjects gave answers on the 5-point Likert scale, from "definitely not" to "definitely yes". The findings of the present study show that a considerable number of the participants tend to exhibit an optimistic bias. This is reflected in their direct statements and in the lack of congruence of their opinions. They do feel the threat of becoming ill but also seem to believe it need not affect them personally. They are also relatively optimistic about the outcomes of the pandemic. At the same time, they realize that COVID-19 may lead to severe psychological, neurological, and mental disorders. The study confirmed a tendency to deny the threat that can pose a severe risk to health and psychological well-being. This is a manifestation of an optimism bias that has its roots in the way the human brain works. The participants did express concerns about the future but at the same time hoped that life after the pandemic would return to normal. It reflects a benevolent facet of self-deception since it makes it possible to cope with highly threatening and impossible to control events.